Tailoring Surgical Intervention By Comparing Outcomes Of Definitive One Stage Vs Staged Repair For Female Anorectal Malformations With Recto Vestibular Fistula - Hubballi, Kaushika; B Kurbet, Santosh (Journal of Neonatal Surgery, 2025)
Background : The corrective management of Anorectal malformations with recto vestibular in female babies by single stage surgery with good surgical yield is a challenge. Here we assess the immediate and mid-term outcomes of definitive repair by single stage vs staged repair in cases of Anorectal malformation with recto -vestibular fistula. Material and Methods : Consecutively patients operated for ARM with Recto vestibular fistula in KLE’s Dr Prabhakar Kore Hospital ,Belagavi were taken in the study.22 patients who met inclusion criteria were included in the study and were divided into 2 Groups by randomization .A prospective comparative study was conducted between Jan 2017 to Dec 2024 with minimum follow up of 5 monthss. RESULTS:[22] Patients were included (Group A:Single stage /primary repair group[11], Group B:Staged surgery group[11]) . Both the groups had a comparable results however the rates of infection and continence issues were slightly more in primary repair patients. Patient compliance and quality of life scoring was better in primary repair patients (Group A). Conclusion-The outcomes of primary repair and multi staged repair for ARM with recto-vestibular fistula were comparable however the long term issues and complications were acceptable in both groups. A systemic review and meta-analysis is required to assess the outcomes in large sample size of patients operated by primary repair (ASARP) procedures.[7]